Transnational Trailblazers of Early Cinema Sarah Bernhardt, Gabrielle Réjane, Mistinguett - Duckett, Victoria (University of California Press, 2023)
At the forefront of the entertainment industries of the late nineteenth and early twentieth centuries were singular actors: Sarah Bernhardt, Gabrielle Réjane, and Mistinguett. Talented women with global ambitions, these performers pioneered the use of film and theatrics to gain international renown. Transnational Trailblazers of Early Cinema traces how these women emerged from the Parisian periphery to become world-famous stars. Through intrepid business prowess and the cultivation of celebrity images, these three artists strengthened ties among countries, continents, and cultures during pivotal years of change.